Dependence of Microstructure and Hardening Behavior on Torsion Strain and Strain Rate in Extruded AZ31 Rods1 . Issue 9 (14th July 2016) - Chen, Hongbing; Liu, Tianmo; Yu, Hongni; Song, Bo; Hou, Dewen; Guo, Ning; He, Jiejun
Abstract : In this study, the effects of torsion strain and strain rate on microstructure and hardening behavior of extruded AZ31 Mg alloy rods are investigated. Torsion deformation can generate abundant extension twins and dislocations and cause the rotation of c‐axis toward extrusion direction. These microstructures exhibit gradient distributions along the radial direction of torsion‐deformed rods. Torsion deformation can effectively enhance the hardness of AZ31 rods. The gradient microstructure leads to a gradient hardness distribution in torsion‐deformed rods. High strain rates can enhance the hardening effect via torsion deformation by promoting increment of dislocation density. Abstract : In this study, torsion deformation is used to enhance the hardness of extruded Mg alloys. Results show that torsion deformation can generate gradient microstructures. The increase of hardness is mainly attributed to dislocation hardening. The high strain rate can enhance the hardening effect by increasing dislocation density.